1996
DOI: 10.1002/mrm.1910350610
|View full text |Cite
|
Sign up to set email alerts
|

NMR studies on human, pathologically changed synovial fluids: Role of hypochlorous acid

Abstract: Recently, it has been reported that hypochlorous acid (HOCl), a special product of neutrophil myeloperoxidase, degrades N-acetyl groups of N-acetylglucosamine, chondroitin sulfate, hyaluronic acid, and minced articular cartilage via a transient product to acetate. This work concerns 1H NMR investigations of synovial fluids of patients with rheumatoid arthritis (RA). Synovial fluids of patients with severe forms of this disease are characterized by enhanced 1H NMR signals for N-acetyl groups (approximately 2.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 23 publications
0
34
0
1
Order By: Relevance
“…Oxidative stress induced by aberrant MPO activity has been observed in infl ammatory lung disease ( 8 ), rheumatoid arthritis ( 9,10 ), peripheral artery disease ( 11 ), cardiovascular disease ( 7,12 ), and diabetes ( 13,14 ). Even basic science studies in rats have shown that MPO directly correlates with severity of myocardial infarction ( 15,16 ).…”
Section: Mpo-mediated Ldl Malondialdehyde Formationmentioning
confidence: 99%
“…Oxidative stress induced by aberrant MPO activity has been observed in infl ammatory lung disease ( 8 ), rheumatoid arthritis ( 9,10 ), peripheral artery disease ( 11 ), cardiovascular disease ( 7,12 ), and diabetes ( 13,14 ). Even basic science studies in rats have shown that MPO directly correlates with severity of myocardial infarction ( 15,16 ).…”
Section: Mpo-mediated Ldl Malondialdehyde Formationmentioning
confidence: 99%
“…A number of studies have used ex vivo nuclear magnetic resonance (NMR) spectroscopy on synovial fluid samples to investigate their metabolic profiles, 3 , 18 , 19 , 20 , 21 and a wide variety of low‐molecular‐mass components with CH2 and CH3 lipid peaks were identified in the samples 18 , 22 , 23 , 24 . In musculoskeletal lesions, the major metabolites are included in lipids with other metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Especially small degradation products like acetate or formate, which are formed when the polysaccharides of cartilage react with hypochlorite (11) or hydroxyl radicals (12), respectively, are difficult to detect. Here, sophisticated methods like high-resolution NMR spectroscopy are more appropriate analytical tools (16,17).…”
Section: Introductionmentioning
confidence: 99%